Investigation of in-situ doping profile for N plus /P/N plus bidirectional switching device using Si1-xGex/Si/Si1-xGex structure - Roh, Il Pyo; Song, Yun Heub; Song, Jin Dong (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2015)
We present a novel junction device with bidirectional current flow for switching devices in a high density spin torque transfer magnetic random access memory (STT-MRAM). In this structure, an N+ type strained SiGe material is adopted as a conduction layer to generate higher electron mobility and a flatter doping profile. A SiGe/Si/SiGe heterojunction structure is also used to obtain a better I-on/I-off ratio due to a steeper junction profile. It is confirmed by 3D simulation that this structure provides higher current drivability and Ion/Ioff ratio. After the simulation, a junction device with N+ Si0.8Ge0.2/P Si/N+ Si0.8Ge0.2 and an area of 4 x 4 um(2) is fabricated and evaluated for bidirectional current flow. From the results obtained, we propose that this bidirectional switching device with a heterojunction structure is a promising candidate for a high density STT-MRAM.